ヒガシ ナンキョク ミズホ カンソク キョテン ニオケル チジョウ キショウ カンソク - 佐々木, 浩; ササキ, ヒロシ; SASAKI, Hiroshi (国立極地研究所, 1974)
P(論文) This paper reports the summary of the data of the surface meteorological observations carried out during the period from June to December in 1972 at Mizuho Camp, East Antarctica. Obtained results are as follows: The differences of the pressures at Mizuho Camp and Syowa Station averaged over ten days and those of the temperatures were 240-265 mb and 13-23℃. The wind speed averaged over ten days was strongest in June and decreased almost linearly from June to December. The frequency distribution of wind speed was of roughly the Gaussian distribution with the peak at about 11 m/s. The prevailing wind direction was ESE and almost the same as the direction of the sastrugi and the slope in the vicinity of Mizuho Camp. The frequency of the prevailing wind direction was about 60% regardless of month. When the wind direction changed counterclockwise from ESE to N, the wind speed decreased and the temperature became higher. The diurnal variation of wind speed was similar to that at Syowa Station. departmental bulletin paper